Parent-Child Interaction Therapy Adapted for Preschoolers with Callous-Unemotional Traits: An Open Trial Pilot Study. (29th March 2019) - Kimonis, Eva R.; Fleming, Georgette; Briggs, Nancy; Brouwer-French, Lauren; Frick, Paul J.; Hawes, David J.; Bagner, Daniel M.; Thomas, Rae; Dadds, Mark
Abstract : Children with co-occurring conduct problems and callous-unemotional (CU) traits show a distinct pattern of early starting, chronic, and aggressive antisocial behaviors that are resistant to traditional parent-training interventions. The aim of this study was to examine in an open trial the acceptability and initial outcomes of a novel adaptation of Parent–Child Interaction Therapy, called PCIT-CU, designed to target 3 distinct deficits of children with CU traits. Twenty-three Australian families with a 3- to 6-year-old ( M age = 4.5 years, SD  = .92) child with clinically significant conduct problems and CU traits participated in the 21-week intervention and 5 assessments measuring child conduct problems, CU traits, and empathy at a university-based research clinic. Treatment retention was high (74%), and parents reported a high level of satisfaction with the program. Results of linear mixed models indicated that the intervention produced decreases in child conduct problems and CU traits, and increases in empathy, with "medium" to "huge" effect sizes ( d s = 0.7–2.0) that maintained at a 3-month follow-up. By 3 months posttreatment, 75% of treatment completers no longer showed clinically significant conduct problems relative to 25% of dropouts. Findings provide preliminary support for using the targeted PCIT-CU adaptation to treat young children with conduct problems and co-occurring CU traits.